PROBLEMATICS OF LEGAL REVIEW (PK) POST POST MK RULING NO 34/PUU-XVII/2019 IN RESOLUTION OF INDUSTRIAL RELATIONS DISPUTES - Saragih, Minggu; Nadirah, Ida (Proceeding International Seminar of Islamic Studies, 2024)
Legal action for judicial review (PK) after the Constitutional Court decision No. 34/PUU-XVII/2019 in resolving industrial relations disputes. The research method uses a normative legal research type, the research approach is a statutory approach, the nature of the research is descriptive, the data source is secondary data, the data collection tool is document study, qualitative data analysis. The elimination of judicial review as an extraordinary legal remedy in resolving industrial relations disputes has an impact on the sense of justice of the parties. It is proven that there is a test of legal norms in Law no. 2 of 2004 concerning Settlement of Industrial Relations Disputes which is considered as the basis for eliminating legal remedies for judicial review with the emergence of the Decision of the Constitutional Court of the Republic of Indonesia Number 34/PUU-XVII/2019. In the research, it was found that the elimination of judicial review in industrial relations dispute cases actually eliminates justice contained in the principles of simple, fast, fair and cheap, it is better that judicial reviews (PK) continue to be held in order to provide space for extraordinary legal remedies as regulated in the Civil Code. The legal remedy for judicial review as an extraordinary measure in industrial relations dispute cases is actually still provided as a manifestation of legal equality and justice. one example that has become permanent law and cannot submit a PK is decision number 779 K/Pdt.Sus-PHI/2022 in the case between PT Belawan Indah against Supatno, Hanafi, Abu Hasan, et al. According to Gustav Radbruch, there are three elements that must always be considered, namely legal certainty, expediency and justice.